Non-competitive reversible inhibition of laccase by H2O2 in osmium mediated layer-by-layer multilayer O2 biocathodes - Grattieri, Matteo (2015)
A systematic study of the inhibition of laccase by hydrogen peroxide in oxygen biocathodes composed of layer-by-layer selfassembled multilayers of Trametes-trogii laccase and osmium derivatized poly(allylamine) redox mediator has been accomplished using a rotating disc electrode at different electrode potentials, oxygen partial pressures and hydrogen peroxide concentrations. The experimental results are consistent with a reversible non-competitive inhibition mechanism in agreement with the Solomon mechanism for laccase previously reported.